Interstellar polarization from CO and XCN mantled grains: A severe test for grain alignment mechanisms - Chrysostomou, A; Hough, J; Whittet, D; Aitken, D; Roche, P; Lazarian, A (Institute of Physics Publishing, 1996)
We present linear spectropolarimetry in the wavelength range 4.5-4.8 μm of the embedded infrared source W33A. Our observations show for the first time the presence of polarization associated with the CO and XCN ice features, demonstrating that the absorbers reside in or on aligned grains. Both narrow and broad components of the solid CO feature near 4.67 μm are polarized. The detection of polarization associated with the narrow CO component is particularly significant, as the ices responsible are thought to exist only in dense, cold regions of molecular clouds, where gas and grain temperatures are expected to be closely coupled and traditional grain alignment mechanisms should become ineffective. We discuss the significance of this result with regard to current grain alignment theories. Mechanisms in which grain rotational energy is enhanced by interaction with cosmic rays merit further investigation. © 1996. The American Astronomical Society. All rights reserved.